Glycolytic flux controls retinal progenitor cell differentiation via regulating Wnt signaling - Joseph Hanna; Yacine Touahri; Alissa Pak; Lauren Belfiore; Edwin van Oosten; Luke Ajay David; Sisu Han; Yaroslav Ilnytskyy; Igor Kovalchuk; Deborah Kurrasch; Satoshi Okawa; Antonio del Sol; et al. (eLife)
Metabolic pathways are remodeled in response to energy and other homeostatic demands and are dynamically regulated during embryonic development, suggesting a role in guiding cellular differentiation. Here, we show that glycolytic flux is required and sufficient to bias multipotent retinal progenitor cells (RPCs) to acquire a rod photoreceptor fate in the murine retina. In RPC-specific Phosphatase and tensin homolog conditional knockout (Pten-cKO) and RPC-specific conditional gain-of-function of dominant active PFKFB3 (cytoPFKFB3) mice, glycolytic gene expression and activity are elevated, correlating with precocious rod photoreceptor differentiation and outer segment (OS) maturation. Conversely, glycolytic inhibition in retinal explants suppresses RPC proliferation and photoreceptor differentiation, achieved either with 2-deoxy-D-glucose, a competitive inhibitor of glucose metabolism, by lowering media pH, which disables PKM2, a rate-limiting enzyme, or by inhibiting lactate/H+ symporters, which lowers intracellular pH. Mechanistically, we show that Wnt signaling, the top-upregulated pathway in Pten-cKO retinas, is a glycolysis-dependent pathway. Pharmacological and genetic perturbation of Wnt signaling by knocking-out Ctnnb1, encoding β-catenin, phenocopies glycolytic inhibition, suppressing RPC proliferation, photoreceptor differentiation, and OS maturation. Thus, developmental rewiring of glycolytic flux modulates Wnt signaling to drive rod photoreceptor differentiation and maturation, an instructive role that may be exploited therapeutically for cell replacement strategies.